Day to day business in a cafe - Garner, Simon; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2005)
This video presents an overview of what is involved in running a cafe such as: a typical day, customers, products, staff, legalities and regulations, operations and location and marketing
Title from title screen
Executive producer, Mark McAuliffe ; editor, Paul Suttherland ; camera, Matthew Lovering ; sound, Wayne Martin
Voice over: Amy Blackmur
DVD format
Keywords: Coffeehouses -- Management; Hospitality industry -- Employees -- Training of